Psychological morbidities among Nepalese migrant workers to Gulf and Malaysia - Sharma, Abha; Adhikari, Renuka; Parajuli, Enjila; Buda, Manisha; Raut, Jyotika; Gautam, Ena; Adhikari, Bibhav (PLOS ONE, 2023)
Background One of the important aftereffects of rapid global development is international mobility, which has placed the health of migrant workers as a key public health issue. A less-developed country, Nepal, with political instability and a significant lack of employment, could not remain untouched by this phenomenon of migration. Our goal was to identify and determine the predictors of anxiety, depression, and psychological wellbeing among Nepalese migrant workers in Gulf countries (United Arab Emirates, Saudi Arabia, Qatar, Oman, Kuwait, Bahrain) and Malaysia. Methods A descriptive cross-sectional study was used to collect information from 502 Nepalese migrant workers in the arrival section of Tribhuvan International Airport from May to June 2019 using purposive sampling. Workers with a minimum work experience of 6 months and above were included in the study. A structured questionnaire with socio-demographic items was used along with the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) and WHO (five) wellbeing scale for measuring the subjective psychological wellbeing and screening for depression. Results The mean age of the respondents was 32.97 years. Majority (41.8%) of the respondents had work experience in Qatar and 63.7% had work experience of 1–5 years. The results suggested that 14.4% had mild to severe depression while 4.4% had a moderate level of anxiety. The WHO5 wellbeing index score suggested that 14.1% of the respondents had a score below 13, which is suggestive of poor psychological wellbeing. Further, the country of work (p = 0.043), sleeping hours (p = 0.001), occupation (p = 0.044), working hours (p = 0.000), water intake (p = 0.010) and anxiety level (p = 0.000) were found to be significantly associated with depression score. Similarly, sleeping hours (p = 0.022), occupation (p = 0.016), working hours (p = 0.000), water intake (p = 0.010), and anxiety level (0.000) were significantly associated with the WHO5 wellbeing score. Conclusions Nepalese migrant workers in the Gulf countries (United Arab Emirates, Saudi Arabia, Qatar, Oman, Kuwait, Bahrain) and Malaysia bear an important burden of psychological morbidities. This highlights the need to prioritize the migrant worker’s mental health by Nepal as well as Gulf countries and Malaysia.